Endometriosis and ovarian cancer: Their association and relationship - Ernesto Bas-Esteve; María Pérez-Arguedas; Gonzalo Ariel Guarda-Muratori; Maribel Acién; Pedro Acién (Elsevier, 2019)
Objectives: To study endometriosis-associated borderline or malignant ovarian epithelial tumors by analyzing their differential clinical features, as well as the histological pattern, survival and immunohistochemical data compared with those without associated endometriosis. Study design: Setting: Hospital Marina Baixa and San Juan University Hospital, Alicante, Spain. This retrospective study included clinical and pathological data from 36 operated cases with endometriosis-associated ovarian epithelial tumors and 305 cases of ovarian epithelial tumors without endometriosis, including borderline and invasive tumors. We also studied hormonal receptors and p53 protein expression in 13 cases with endometriosis-associated endometrioid and clear cell tumors, and report two cases with histologically-confirmed previous endometriosis. Results: Associated endometriosis was observed in 10.5% of patients with borderline or invasive ovarian epithelial tumor, 53% of those with endometrioid, and 22% with clear cell tumors. Patients with endometriosis-associated ovarian epithelial tumors were younger, had lower parity, were more frequently premenopausal, had a lower tumor stage or were borderline, and in general had better prognosis and longer survival, although they also more frequently had an associated endometrial carcinoma. Associated endometriosis and endometrioid tumors were generally estrogen-receptor positive, whereas they were negative in the clear cell tumor component. p53 protein positivity was generally observed in clear cell tumors and in associated endometriosis. Two reported cases with previous, known endometriosis were followed in their evolution to borderline endometrioid carcinoma and clear cell carcinoma, respectively. Conclusions: Our results and review of the literature suggest that the association of ovarian epithelial tumors and endometriosis is a factor for good prognosis for ovarian cancer and that this association might correspond in many cases to an intermediate stage in the development of endometriosis to endometrioid, clear cell, or other invasive carcinomas. Keywords: Endometriosis, Ovarian cancer, Endometrioid, Clear cell, Borderline, Ovarian tumors